2012
DOI: 10.1177/1089313x1201600401
|View full text |Cite
|
Sign up to set email alerts
|

Assessing and Reporting Dancer Capacities, Risk Factors, and Injuries

Abstract: This technical report of the Standard Measures Consensus Initiative of the In-ternational Association for Dance Medicine and Science (IADMS) describes the results of the committees multi-year effort to synthesize information regarding the tests and measures used in dance-related research, protocols for reporting injuries, and appropriate use of available technolo-gies to aid in standardizing such matters. Specific recommendations are presented, with accompanying rationales, to facilitate consensus among member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(12 citation statements)
references
References 85 publications
0
12
0
Order By: Relevance
“… Values are means (95% confidence intervals) unless otherwise indicated. a Values are mean (SD). b Values are proportion (%). c Previous injury was operationally defined as any dance-related physical complaint that required medical attention and/or time-loss (i.e., caused the dancer to miss more than 1 day of class, rehearsal or performance) in the previous 1-year. 15,16 d Previous injury data was missing for one participant. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… Values are means (95% confidence intervals) unless otherwise indicated. a Values are mean (SD). b Values are proportion (%). c Previous injury was operationally defined as any dance-related physical complaint that required medical attention and/or time-loss (i.e., caused the dancer to miss more than 1 day of class, rehearsal or performance) in the previous 1-year. 15,16 d Previous injury data was missing for one participant. …”
Section: Methodsmentioning
confidence: 99%
“… c Previous injury was operationally defined as any dance-related physical complaint that required medical attention and/or time-loss (i.e., caused the dancer to miss more than 1 day of class, rehearsal or performance) in the previous 1-year. 15,16 …”
Section: Methodsmentioning
confidence: 99%
“…The athletic trainer (AT) for the School of Dance recorded dancers’ DEHr, with a DEHr defined as 1 hour of dance participation in class, rehearsal, or performance. 23 Class was defined as the dancers’ regular modern and/or ballet technique class. Rehearsal was non-class time devoted to a later performance (ie, residency, student pieces, etc.).…”
Section: Methodsmentioning
confidence: 99%
“…Negative stressors in ballet dancers' lives have been shown to predict an increased injury rate. [1][2][3][4] It has been shown that male dancers demonstrate significantly more negative personality traits and psychological distress than female dancers or men • • Harmful behaviors associated with SOGI should be taken into consideration as part of a biopsychosocial model of health in order to improve outcomes and quality of life. • • Healthcare providers should have the tools necessary to screen at-risk groups for harmful behaviors in order to mitigate health risks.…”
Section: Introductionmentioning
confidence: 99%